Composition and reinforcement method

A composition of water-soluble calcium salt, silane compound, and water, combined with an alkali metal silicate surface treatment, addresses the penetration and strengthening of deteriorated concrete structures, enhancing durability and appearance.

JP7603403B2Active Publication Date: 2024-12-20F CONSULTANT
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020158474
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-01
Filing Date
2020-09-23
Publication Date
2024-12-20
Estimated Expiration
2040-09-23

AI Technical Summary

Technical Problem

Existing concrete structures deteriorate over time due to salt damage and carbonation, leading to cracking and peeling, and current repair methods fail to adequately penetrate calcium salts into the concrete interior.

Method used

A composition comprising a water-soluble calcium salt, a water-soluble silane compound, and water, which enhances calcium ion permeability and strength by applying the composition to the concrete structure, followed by a surface reinforcing agent containing alkali metal silicate.

Benefits of technology

The solution increases calcium ion penetration, repairs and strengthens concrete structures, particularly deteriorated ones, while providing excellent waterproof properties and aesthetic appearance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007603403000001
    Figure 0007603403000001
  • Figure 0007603403000002
    Figure 0007603403000002
Patent Text Reader

Abstract

To provide a composition capable of impregnating calcium component fully to a concrete structure.SOLUTION: The reinforcement method of the concrete structure is a composition which is adhered to the concrete structure and comprises water soluble calcium salt, water soluble silane compound and water. The reinforcement method of the concrete structure comprises an adhesion of a surface reinforcement agent including at least alkaline metal silicate salt.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a novel composition for use in concrete structures. [Background technology]

[0002] Conventionally, many concrete structures have been used in bridges, tunnels, elevated roads, buildings, etc. However, concrete structures have problems such as deterioration over time due to salt damage, neutralization, frost damage, etc., which causes cracks and peeling of concrete pieces in the structures. For this reason, many methods for repairing and reinforcing concrete structures have been proposed.

[0003] For example, Japanese Patent Application Laid-Open No. 11-193638 (Patent Document 1) discloses a crack repair agent for concrete structures, which is an aqueous solution of a calcium salt to which alcohol has been added. However, the repair agent of Patent Document 1 is rapidly dried by the action of alcohol to form calcium salt crystals, and therefore may not sufficiently penetrate the calcium salt into the interior of the concrete structure. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 11-193638 Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention has been made in view of the above circumstances, and has an object to obtain a composition capable of sufficiently impregnating a concrete structure with a calcium component. [Means for solving the problem]

[0006] Means for Solving the Problems of the Prior Art The inventors of the present invention have conducted intensive research in view of the above-mentioned problems of the prior art, and as a result have come up with the idea of ​​a composition comprising a water-soluble calcium salt, a water-soluble silane compound, and water, thereby completing the present invention.

[0007] That is, the present invention has the following features. 1. A composition to be applied to a concrete structure, comprising a water-soluble calcium salt, a water-soluble silane compound, and water; The water-soluble calcium salt is 、 Calcium nitrite in 1. A composition according to claim 1, wherein the water-soluble silane compound comprises an amino group-containing silane compound. 2. The composition according to claim 1, wherein the water-soluble silane compound comprises an amino group-containing silane compound. 3. A method for reinforcing a concrete structure, comprising applying to the concrete structure the composition according to claim 1 or 2. 4. A method for reinforcing a concrete structure, comprising applying to the concrete structure the composition according to claim 1 or 2, and then applying to the concrete structure a surface reinforcing agent containing at least an alkali metal silicate. Effect of the Invention

[0008] According to the present invention, it is possible to further increase the permeability of calcium salts (calcium ions) into concrete structures, thereby enabling the strength of concrete structures, particularly deteriorated concrete structures, to be repaired, and the surface strength to be increased. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, an embodiment of the present invention will be described.

[0010] (composition) The present invention relates to a composition to be applied to a concrete structure, and is a composition suitable as an impregnating reinforcing agent for a concrete structure, which is capable of replenishing calcium ions inside the concrete structure, repairing deteriorated parts, and increasing surface strength by applying the composition to the concrete structure, particularly to a deteriorated concrete structure. Such a composition is characterized by containing (A) a water-soluble calcium salt, (B) a water-soluble silane compound, and water.

[0011] The concrete structure may be, for example, a bridge, a tunnel, an elevated road, a building, etc., which is made of cement, mortar, etc., and may be either a new or existing concrete structure. The composition of the present invention is suitable for existing concrete structures, particularly deteriorated concrete structures in which neutralization has progressed due to aging, calcium components have eluted due to rainfall, or cracks have occurred.

[0012] The water-soluble calcium salt (A) of the present invention (hereinafter also referred to as "component (A)") is a component that replenishes calcium ions in voids inside a concrete structure. Component (A) of the present invention is a calcium salt that is soluble in water at 25°C at 1% by weight or more, and examples of such calcium salt include calcium chloride, calcium nitrate, calcium nitrite, and calcium acetate. These can be used alone or in combination of two or more. In the present invention, it is preferable to contain one selected from calcium nitrate, calcium nitrite, and the like. In particular, when calcium nitrite is contained, it is preferable because the action of the nitrite ions provides a rust-preventive effect on the reinforcing bars inside the concrete structure.

[0013] The content of component (A) in the composition is preferably 1 to 50% by weight (more preferably 2 to 40% by weight, and even more preferably 3 to 20% by weight). When this range is satisfied, a sufficient amount of calcium ions can be replenished inside the concrete structure.

[0014] The composition of the present invention is characterized by including (B) a water-soluble silane compound (hereinafter also referred to as "component (B)") as an essential component. In the present invention, the use of the above-mentioned components (A) and (B) in combination can enhance the penetration (impregnation) of the above-mentioned component (A) into the interior of a concrete structure. As a result, calcium ions do not accumulate near the surface of the concrete structure immediately after application, but penetrate deep into the concrete structure, and sufficient calcium ions can be replenished, so that a sufficient penetration depth and penetration amount for repair can be secured. Furthermore, the component (B) that has penetrated into the interior of the concrete structure reacts with the constituent components (cement, etc.) of the concrete structure, thereby increasing its strength. Furthermore, by including the component (B), when a surface strengthening agent containing an alkali metal silicate is applied as the next step, it becomes possible to penetrate the surface strengthening agent into the interior (deep) of the concrete structure, thereby further increasing the strength of the concrete structure and imparting excellent waterproofing properties.

[0015] The component (B) of the present invention may be any component that dissolves in water, and is preferably capable of preparing a 1% by weight aqueous silane solution. When preparing the 1% by weight aqueous silane solution, the pH may be adjusted as necessary. Examples of such a component (B) include: Epoxy group-containing silane compounds such as glycidoxymethyltrimethoxysilane, glycidoxymethyltriethoxysilane, β-glycidoxyethyltrimethoxysilane, β-glycidoxyethyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-glycidoxypropylmethyldimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, γ-glycidoxypropyldimethylmethoxysilane, γ-glycidoxypropyl(ethyl)dimethoxysilane, β-3,4-epoxycyclohexylethyltrimethoxysilane, β-3,4-epoxycyclohexylethyltriethoxysilane, 8-glycidoxyoctyltrimethoxysilane, 8-glycidoxyoctylmethyldimethoxysilane, and 8-glycidoxyoctylmethyldiethoxysilane;

[0016] γ-Aminopropyltrimethoxysilane, γ-Aminopropyltriethoxysilane, γ-Aminopropyltriisopropoxysilane, γ-Aminopropylmethyldimethoxysilane, γ-Aminopropylmethyldiethoxysilane, N-β(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β(aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-β(aminoethyl)-γ-aminopropyltriethoxysilane, N-β(aminoethyl)-γ-aminopropylmethyldiethoxysilane, N-β(aminoethyl)-γ- Amino group-containing silane compounds such as aminopropyltriisopropoxysilane, N-phenyl-γ-aminopropyltrimethoxysilane, γ-ureidopropyltrimethoxysilane, γ-anilinopropyltrimethoxysilane, γ-ureidopropyltrimethoxysilane, N-phenyl-γ-aminopropyltrimethoxysilane, N-vinylbenzyl-γ-aminopropyltriethoxysilane, N-β(aminoethyl)-8-aminooctyltrimethoxysilane, and γ-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine;

[0017] (meth)acryl group-containing silane compounds, such as 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane, and 3-(meth)acryloxypropyltriethoxysilane; Other examples include 3-mercaptopropyltrimethoxysilane, bis(triethoxysilylpropyl)tetrasulfide, and 3-isocyanatepropylethoxysilane, etc. These can be used alone or in combination of two or more.

[0018] Among these, in the present invention, it is preferable to contain an amino group-containing silane compound as component (B). This further enhances the penetration (impregnation) properties of component (A) and inhibits calcium components from accumulating on the surface of the concrete structure. In addition, after application, there is no uneven application or surface whitening, and the appearance is excellent. The content of the amino group-containing silane compound in component (B) is preferably 50% by weight or more (more preferably 80% by weight or more), and the composition may be composed of only the amino group-containing silane compound.

[0019] The content of component (B) in the composition is preferably 0.01 to 5% by weight (more preferably 0.05 to 5% by weight). When this range is satisfied, the permeability of component (A) into the concrete structure can be increased, and the surface strength can be further increased.

[0020] The composition of the present invention is prepared by dissolving the above-mentioned components (A) and (B) in water. The content of water in the composition is the remaining amount excluding the above-mentioned components (A) and (B), and is preferably 45 to 98.99% by weight (more preferably 55 to 97.95% by weight).

[0021] The composition of the present invention may contain known additives as necessary, so long as they do not significantly impair the effects of the present invention. Examples of such additives include thickeners, leveling agents, wetting agents, antifreeze agents, preservatives, antifungal agents, anti-algae agents, antibacterial agents, deodorants, dispersants, antifoaming agents, adsorbents, flame retardants, coloring pigments, extender pigments, fibers, water repellents, ultraviolet absorbing agents, light stabilizers, antioxidants, catalysts, etc.

[0022] (Reinforcement method) The present invention relates to (1) applying the composition to a concrete structure; This composition contains the compound, which can reinforce the concrete structure and increase its surface strength. It is particularly suitable for existing deteriorated concrete structures.

[0023] In the above step (1), the method of applying the composition is not particularly limited, and various methods such as brush coating, roller coating, spray coating, etc. can be used. When coating is performed in a factory, a roll coater, a flow coater, etc. can also be used for coating. Furthermore, the composition can be injected into cracks, etc., using a cylinder, etc.

[0024] The amount of the composition applied is preferably 0.01 to 0.5 kg / m 2 (More preferably 0.03 to 0.4 kg / m 2 , and more preferably 0.05 to 0.3 kg / m 2 ) is about. When such a range is satisfied, the effect of the present invention can be sufficiently obtained. Also, when the composition is applied at or below the upper limit, discoloration of the concrete surface can be suppressed. The number of times the composition is applied may be appropriately set depending on the state of the concrete structure (such as the degree of deterioration), but is preferably 1 to 2 times. Also, water can be sprayed on the surface of the concrete structure after the composition is applied. In the present invention, since the composition contains the (B) component, the (A) component is more likely to penetrate (impregnate) into the interior of the concrete structure together with the sprayed water, and the effect of the present invention can be enhanced. Furthermore, since the composition is less likely to remain on the surface, discoloration can also be suppressed. The drying time of the composition is preferably 1 hour or more. Also, the drying temperature is preferably 0°C or more and 50°C or less, more preferably 5°C or more and 40°C or less.

[0025] Furthermore, following the above step (1), (2) applying a surface enhancing agent containing at least an alkali metal silicate; It is preferable to carry out the process (2) above. The surface strength of the concrete structure can be further increased by the process (2). In particular, by applying a surface strengthening agent containing an alkali metal silicate after the process (1) above, it becomes possible for the surface strengthening agent to penetrate into the interior (deep part) of the concrete structure, and the strength of the concrete structure can be further increased. Furthermore, since the surface strengthening agent can be uniformly penetrated (impregnated), uneven gloss and the like are unlikely to occur, and a finish with excellent aesthetics can be obtained.

[0026] The (C) alkali metal silicate (hereinafter also referred to as "component C") contained in the surface strengthening agent penetrates (impregnates) the inside of a concrete structure to form a hardened body, thereby improving the surface strength of the concrete structure. As the (C) component, any water-soluble alkali metal silicate (also referred to as "water glass") represented by the general formula: M2O·nSiO2 (M is at least one alkali metal selected from Li, K, Na, and Cs) can be used. As the (C) component, for example, sodium silicate, sodium orthosilicate, sodium metasilicate, lithium silicate, potassium silicate, etc. can be mentioned. In addition, water glass that is commercially available as an aqueous solution of an alkali metal silicate can also be used. The above alkali metal silicates may be used alone or in a mixture of two or more kinds.

[0027] The content of the component (C) in the surface strengthening agent is preferably 5 to 60% by weight (more preferably 8 to 50% by weight) calculated as the effective components (M2O and SiO2) in the surface strengthening agent. When the content is within this range, the surface strength can be increased and excellent aesthetics can be obtained.

[0028] In the present invention, it is preferable that the component (C) contains at least sodium silicate with a SiO2 / Na2O (molar ratio) of 5 / 1 to 2 / 1 (more preferably 4 / 1 to 3 / 1). In such a case, the effect of the present invention can be further enhanced. Furthermore, in the present invention, potassium silicate with a SiO2 / K2O (molar ratio) of 5 / 1 to 1 / 1 (more preferably 4 / 1 to 1 / 1) and lithium silicate with a SiO2 / Li2O (molar ratio) of 5 / 1 to 2 / 1 (more preferably 5 / 1 to 3 / 1) can be mixed and used. This enhances the permeability to the concrete structure, and a dense hardened body can be formed. The reinforcing method of the present invention enhances the waterproofing of the concrete structure, and can effectively suppress deterioration due to the penetration of water such as rainfall. Furthermore, it is possible to suppress the elution of alkali metals and prevent efflorescence on the surface of the concrete structure.

[0029] In the present invention, it is particularly preferable to use a mixture of sodium silicate and potassium silicate. The mixing ratio of sodium silicate and potassium silicate is SiO2 / (Na2O+K2O) (molar ratio) of 5 / 1 to 1 / 1 (preferably 4 / 1 to 2.5 / 1), and it is preferable to adjust the content of SiO2 to 50% by weight (more preferably 10 to 30% by weight) based on the entire surface strengthening agent. In this case, the content of sodium silicate (effective ingredient equivalent) in the (C) component is preferably 10 to 98% by weight (more preferably 30 to 95% by weight or more), and the content of potassium silicate (effective ingredient equivalent) is preferably 2 to 90% by weight (more preferably 5 to 70% by weight), so that they can be adjusted to the above ranges. When the content is within such a range, the surface strength can be further increased and excellent aesthetics can be obtained.

[0030] Furthermore, it is also preferable to use lithium silicate in a mixed state. In this case, it is preferable to adjust the mixing ratio of sodium silicate, potassium silicate, and lithium silicate so that SiO2 / (Na2O+K2O+Li2O) (molar ratio) is 5 / 1 to 1 / 1 (preferably 4 / 1 to 2 / 1), and the content of SiO2 is 5 to 50% by weight (more preferably 10 to 30% by weight) relative to the entire surface strengthening agent. In this case, the content of sodium silicate (converted into active ingredient) in the (C) component is preferably 30 to 98% by weight (more preferably 50 to 95% by weight or more), the content of potassium silicate (converted into active ingredient) is preferably 1.5 to 50% by weight (more preferably 4 to 40% by weight), and the content of lithium silicate (converted into active ingredient) is preferably 0.5 to 40% by weight (more preferably 1 to 30% by weight), so that the above ranges can be adjusted. When the content is within such a range, water resistance is increased, and appearance abnormalities such as whitening and gloss change due to penetration of water such as rainfall can be effectively suppressed.

[0031] In the present invention, the surface strengthening agent preferably contains a silane compound similar to the component (B). The content of the component (B) in the surface strengthening agent is preferably 0.01 to 5% by weight (more preferably 0.05 to 5% by weight). This allows the surface strengthening agent (component (C)) to easily penetrate into the interior (deep part) of the concrete structure, further enhancing the effect of the present invention. Furthermore, since the surface strengthening agent can be uniformly penetrated (impregnated), uneven gloss and the like are unlikely to occur, and a finish with excellent aesthetics can be obtained.

[0032] The surface strengthening agent of the present invention is prepared by dissolving the above-mentioned components (C) and (B) in water. The content of water in the surface strengthening agent is the remaining amount excluding the active ingredients of the above-mentioned components (C) and (B), and is preferably 45 to 95% by weight (more preferably 50 to 90% by weight).

[0033] The above surface strengthening agent may contain known additives as necessary, so long as they do not significantly impair the effects of the present invention. Examples of such additives include thickeners, leveling agents, wetting agents, antifreeze agents, preservatives, antifungal agents, anti-algae agents, antibacterial agents, deodorants, dispersants, antifoaming agents, adsorbents, flame retardants, coloring pigments, extender pigments, fibers, water repellents, ultraviolet absorbers, light stabilizers, antioxidants, catalysts, etc.

[0034] In the above step (2), the method of applying the surface strengthening agent is not particularly limited, and various methods can be used, such as brush coating, roller coating, spray coating, etc. When coating is performed in a factory, a roll coater, a flow coater, etc. can also be used in addition to the above.

[0035] The amount of the surface strengthening agent applied is preferably 0.01 to 0.5 kg / m 2 (More preferably 0.05 to 0.4 kg / m 2 ) The number of times the surface strengthening agent is applied may be appropriately determined depending on the condition of the concrete structure (such as the degree of deterioration), but is preferably 1 to 2 times. After application of the surface strengthening agent, water may be sprayed on the surface to enhance permeability. This makes it possible to obtain a finish with excellent aesthetics and with less occurrence of uneven gloss. The drying time of the surface strengthening agent is preferably 1 hour or more. The drying temperature is preferably 0°C or higher and 50°C or lower, more preferably 5°C or higher and 40°C or lower. EXAMPLES

[0036] The following examples will clarify the features of the present invention.

[0037] The following raw materials were used: Component (A) (A1) Calcium nitrite (B) Component (B1) N-β(aminoethyl)-γ-aminopropyltrimethoxysilane (B2) γ-aminopropyltrimethoxysilane (C) Component (C1) Sodium silicate aqueous solution Active ingredient: 33.0% (SiO2=26.0%, Na2O=7.0%) SiO2 / Na2O (molar ratio) = 3.83 (C2) Potassium silicate aqueous solution Active ingredient: 55.0% (SiO2=28.0%, K2O=22.0%) SiO2 / K2O (molar ratio) = 1.99 (C3) Lithium silicate aqueous solution Active ingredient: 23.3% (SiO2=20.4%, Li2O=2.9%) SiO2 / Li2O (molar ratio) = 3.50

[0038] <Preparation of Composition> ·Composition 1 Composition 1 was obtained by adding 0.1 parts by weight of (B1) N-β(aminoethyl)-γ-aminopropyltrimethoxysilane to 100 parts by weight of a 15% by weight aqueous solution of calcium nitrite (A1) dissolved in water and stirring. ·Composition 2 Composition 2 was obtained by adding 0.1 parts by weight of (B2) γ-aminopropyltrimethoxysilane to 100 parts by weight of a 15% by weight aqueous solution of calcium nitrite obtained by dissolving (A1) calcium nitrite in water and stirring the mixture. ·Composition 3 Composition 3 was obtained by adding 0.3 parts by weight of (B1) N-β(aminoethyl)-γ-aminopropyltrimethoxysilane to 100 parts by weight of a 15% by weight aqueous solution of calcium nitrite (A1) dissolved in water and stirring the mixture. ·Composition 4 Composition 4 was obtained by adding 1 part by weight of (B1) N-β(aminoethyl)-γ-aminopropyltrimethoxysilane to 100 parts by weight of a 15% by weight aqueous solution of calcium nitrite (A1) dissolved in water and stirring the mixture. ·Composition 5 Composition 5 was obtained by adding 8 parts by weight of (B1) N-β(aminoethyl)-γ-aminopropyltrimethoxysilane to 100 parts by weight of a 15% by weight aqueous solution of calcium nitrite (A1) dissolved in water and stirring. ·Composition 6 Composition 6 was obtained by adding 0.3 parts by weight of (B1) N-β(aminoethyl)-γ-aminopropyltrimethoxysilane to 100 parts by weight of a 5 wt % calcium nitrite aqueous solution obtained by dissolving (A1) calcium nitrite in water and stirring the mixture. ·Composition 7 Composition 7 was obtained by adding 0.3 parts by weight of (B1) N-β(aminoethyl)-γ-aminopropyltrimethoxysilane to 100 parts by weight of a 20% by weight aqueous solution of calcium nitrite (A1) dissolved in water and stirring. ·Composition 8 Composition 8 was obtained by adding 0.3 parts by weight of (B1) N-β(aminoethyl)-γ-aminopropyltrimethoxysilane to 100 parts by weight of a 45% by weight aqueous solution of calcium nitrite (A1) dissolved in water and stirring. ·Composition 9 (A1) Composition 9 was a 15 wt % aqueous calcium nitrite solution obtained by dissolving calcium nitrite in water. ·Composition 10 (A1) A 45 wt % aqueous calcium nitrite solution obtained by dissolving calcium nitrite in water was used as composition 10. ·Composition 11 (A1) Composition 11 was obtained by adding 1.0 part by weight of ethanol to 100 parts by weight of a 15% aqueous calcium nitrite solution obtained by dissolving calcium nitrite in water and stirring the mixture. ·Composition 12 (A1) Composition 12 was obtained by adding 0.1 part by weight of a surfactant (sodium alkylbenzene sulfonate) to 100 parts by weight of a 15% by weight aqueous solution of calcium nitrite obtained by dissolving calcium nitrite in water and stirring the mixture.

[0039] <Preparation of Surface Strengthening Agent> Surface enhancer 1 (C1) A surface treatment agent 1 was prepared by mixing 70 parts by weight of an aqueous sodium silicate solution and 30 parts by weight of water. Surface strengthening agent 2 Surface treatment agent 2 was prepared by mixing 70 parts by weight of (C1) sodium silicate aqueous solution, 0.5 parts by weight of (B1) N-β(aminoethyl)-γ-aminopropyltrimethoxysilane, and 29.5 parts by weight of water. Surface enhancer 3 Surface treatment agent 3 was prepared by mixing 60 parts by weight of (C1) sodium silicate aqueous solution, 10 parts by weight of (C2) potassium silicate aqueous solution, 0.5 parts by weight of (B1) N-β(aminoethyl)-γ-aminopropyltrimethoxysilane, and 29.5 parts by weight of water. Surface enhancer 4 Surface strengthening agent 4 was obtained by adding and stirring 55 parts by weight of (C1) sodium silicate aqueous solution, 10 parts by weight of (C2) potassium silicate aqueous solution, 5 parts by weight of (C3) lithium silicate aqueous solution, 0.5 parts by weight of (B1) N-β(aminoethyl)-γ-aminopropyltrimethoxysilane, and 29.5 parts by weight of water.

[0040] <Test Example [I]> ·Base material Standard mortar (100 x 100 x 20 mm) was left to stand in a 5% CO2 atmosphere for 60 days and neutralized to prepare the base material.

[0041] Penetration rating 1 Compositions 1 to 12 were each applied to the above substrate in an amount of 0.1 kg / m 2 The paint was applied with a brush, and the speed of penetration into the substrate was observed and compared with the application of water (blank). The evaluation criteria were the following three levels (A: excellent, B: poor, C: poor). The results are shown in Table 1. A: It penetrates faster than water. B: Penetrates as quickly as water. C: Penetrates slower than water.

[0042] Penetration rating 2 Compositions 1 to 12 were each applied to the above substrate in an amount of 0.1 kg / m 2The specimens were then brushed with calcium nitrite and cured at room temperature (25°C, 60% Rh) for 24 hours. The specimens were then cut and dried for a further 24 hours, after which the penetration depth of the calcium nitrite on the cut surface was measured. (Note that the area that had been permeated with calcium nitrite was the area that turned pale yellow after drying.) The evaluation criteria were as follows: A>B>C (Excellent), with three levels. The results are shown in Table 1. A: 2mm or more B: 1.5mm or more and less than 2mm C: Less than 1.5 mm

[0043] Aesthetic evaluation Compositions 1 to 12 were each applied to the above substrate in an amount of 0.1 kg / m 2 The specimens were then brushed with 100% ethyl alcohol and left to cure for 24 hours at room temperature (25°C, 60% Rh). The surfaces of the specimens were visually evaluated for the presence or absence of appearance abnormalities such as uneven gloss and uneven hue. The evaluation criteria were as follows: A>B>C (excellent). The results are shown in Table 1. A: The finish is uniform and there are no abnormalities. B: Slight abnormalities are observed. C: Clear abnormalities are observed.

[0044] [Table 1]

[0045] In the test examples I-1 to I-8, good results were obtained in the permeability evaluation and the aesthetic evaluation. In particular, in the test examples I-1 to I-4, I-6, and I-7, all the evaluations were rated as A, which was an excellent result. On the other hand, in the test examples I-9 to I-11, the results were not sufficient. In addition, the test example I-12 had a slightly inferior result in the permeability evaluation 2.

[0046] <Test Example II> According to the combination of the composition and the surface enhancing agent shown in Table 2, the composition was applied to the above substrate in an amount of 0.1 kg / m 2 After aging for 24 hours at room temperature (25°C, 60% Rh), a surface strengthening agent was applied at a rate of 0.2 kg / m 2The test specimens were then aged at room temperature (25°C) for 7 days and evaluated as follows. The results are shown in Table 2.

[0047] Aesthetic evaluation The surface of the test specimen was visually evaluated for the presence or absence of abnormalities in appearance such as uneven gloss, uneven hue, etc. The evaluation criteria were the following three levels (A: excellent, B: poor, C: excellent). A: The finish is uniform and there are no abnormalities. B: Slight abnormalities are observed. C: Clear abnormalities are observed.

[0048] Abrasion resistance (surface strength) evaluation The abrasion loss of the obtained specimens was observed after 500 revolutions using a Taber type tester, an abrasion wheel CS-17, and a load of 1000g, in accordance with JIS K5600 5.9 Abrasion Resistance (Abrasion Wheel Method). The abrasion loss was compared with that of an untreated slate board and evaluated. The evaluation criteria were the following three levels (A: excellent, B: poor, C: excellent). A: Better than untreated B: Slightly better than untreated C: Equivalent to or less than untreated

[0049] Penetration depth evaluation The surface of the obtained test specimen is ground every 1 mm in depth. Water is added so that the obtained ground powder becomes 5%, and the mixture is stirred for 10 minutes and left to stand for 24 hours to extract sodium (Na) into the water. The amount of Na is measured using a Na ion meter, and it is determined that the material has penetrated to a depth where the amount of Na is 30% or more higher than that of uncoated mortar, and the penetration depth is calculated. The evaluation criteria were the following three levels (A: excellent>B>C: poor). A: 2mm or more B: 1mm or more and less than 2mm C: Less than 1 mm

[0050] Water permeability (waterproofing) rating The obtained test specimens were evaluated for water permeability according to JIS A 6909 7.13 (water permeability test method B). They were compared with a standard uncoated mortar board and evaluated. The evaluation criteria were the following three levels (excellent: A>B>C: poor). The results are shown in Table 2. A: Low water permeability B: Equivalent C: High water permeability

[0051] [Table 2]

[0052] In the test examples II-1 to II-5, the permeability of the surface strengthening agent was good, and good results were obtained in the aesthetic evaluation, the abrasion resistance evaluation, the penetration depth, and the water permeability (waterproofness) evaluation. In particular, in the test examples II-2 to II-5, the permeability of the surface strengthening agent was excellent, and all evaluations were rated A. On the other hand, in the test example II-6, the permeability of the surface strengthening agent was poor, and sufficient results were not obtained. In addition, in the test example II-7, the amount of water permeation was high, and sufficient waterproofness was not obtained.

Claims

1. A composition to be applied to a concrete structure, comprising a water-soluble calcium salt, a water-soluble silane compound, and water, The composition, wherein the water-soluble calcium salt is calcium nitrite.

2. 2. The composition according to claim 1, wherein the water-soluble silane compound comprises an amino group-containing silane compound.

3. A method for reinforcing a concrete structure, comprising applying the composition according to claim 1 or 2 to the concrete structure.

4. 3. A method for reinforcing a concrete structure, comprising applying the composition according to claim 1 or 2 to the concrete structure, and then applying a surface reinforcing agent containing at least an alkali metal silicate.

Citation Information

Patent Citations

  • Method for preventing deterioration of hardened cement

    JP1990307879A

  • Crack repairing agent and waterproofing and repairing construction method for concrete structure, and improving method for concrete

    JP1999193638A

  • Aqueous composition that forms flexible film

    JP2011057844A

  • Method for inhibiting deterioration of reinforced concrete

    JP2018172950A

  • Aqueous coating material

    JP2019157124A